Kesulitan Anak Usia Dini pada Pembelajaran Pendidikan Agama Islam - Apriyani Lestari Kudadiri (Madaniyah, 2019)
This research was conducted in two early childhood education institutions, namely TK Mashitoh Ketegan and RA Hidayatul Qur'an. The research method used is a qualitative method. The technique of collecting data uses observation and interviews. The results of the study showed that there were difficulties in learning PAI and teacher difficulties and teaching them, in terms of 3 aspects, namely aspects of students, aspects of the teacher, and also from the aspects of facilities and infrastructure.